2011
DOI: 10.1007/s00421-011-2109-7
|View full text |Cite
|
Sign up to set email alerts
|

The ACTN3 genotype in soccer players in response to acute eccentric training

Abstract: Genetic factors can interfere with sporting performance. The identification of genetic predisposition of soccer players brings important information to trainers and coaches for individual training loads adjustment. Different responses to eccentric training could be observed by the genotype referred to as α-actinin-3 (ACTN3) in biomarkers of muscle damage, hormones and inflammatory responses. The aim of this study was to compare acute inflammatory responses, muscle damage and hormonal variations according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
81
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 63 publications
(85 reference statements)
10
81
0
2
Order By: Relevance
“…The result of this study is also in accordance with the Brazilian study [10]. Another recent study by Pimenta et al, in which 37 professional soccer players were examined, showed a prevalence of 40.5% for the RR genotype [25], which agrees with our results.…”
Section: Discussionsupporting
confidence: 93%
“…The result of this study is also in accordance with the Brazilian study [10]. Another recent study by Pimenta et al, in which 37 professional soccer players were examined, showed a prevalence of 40.5% for the RR genotype [25], which agrees with our results.…”
Section: Discussionsupporting
confidence: 93%
“…This study and those that were previously presented, corroborate the ideas of Urhausen and Kindermann 34 , who claimed that CK concentration represents exercise-induced mechanical wear due to the exercise performed in previous days and is linked to training intensity and volume. Hence, for the development of a training program, it is imperative to assess an athlete's muscular stress using indicators, such as CK, considering that the results can guide the type of specific training required for each player in order to prevent overtraining and ensure that the training will improve, or at least maintain, performance.…”
Section: Discussionsupporting
confidence: 91%
“…The authors also verified that 24 hours after the match, IL-6 levels had already returned to baseline values. Moreover, Pimenta et al 10 , who also identified significant changes in IL-6 concentrations in soccer players after a battery of plyometric jumps, verified that IL-6 values returned to baseline 2 hours after the activity. The same kinetic behavior of increased post-activity IL-6 was observed in female soccer players 4 .…”
Section: Discussionmentioning
confidence: 85%
“…High-intensity activities and with high demand on the muscle skeletal system, such as soccer, result in high levels of muscle microtrauma and the release of inflammatory and muscle damage markers 6,10 . Microtrauma and damage can be determined by measuring IL-6 6,10 , CK 13 and alpha-actin 11,12 , all of which are present in the blood and result from muscle rupture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation